INTERACTIVE EFFECTS OF AEROBIC FITNESS, STRENGTH AND OBESITY ON MORTALITY IN MEN - Crump, Casey (Am J Prev Med, 2016)
INTRODUCTION: Low aerobic fitness, low muscular strength, and obesity have been associated with premature mortality, but their interactive effects are unknown. This study examined interactions among these common, modifiable factors, which may help inform more effective preventive interventions. METHODS: A national cohort study was conducted of all 1,547,478 military conscripts in Sweden during 1969–1997 (97–98% of all 18-year-old males each year). Aerobic fitness, muscular strength, and body mass index (BMI) measurements were examined in relation to all-cause and cardiovascular mortality through 2012 (maximum age 62). Data collection/analysis were in 2015–2016. RESULTS: Low aerobic fitness, low muscular strength, and obesity at age 18 were independently associated with higher all-cause and cardiovascular mortality in adulthood. The combination of low aerobic fitness and muscular strength (lowest vs. highest tertiles) was associated with 2-fold all-cause mortality (adjusted hazard ratio, 2.01; 95% CI, 1.93–2.08; P<0.001; mortality rates per 100,000 person-years, 247.2 vs. 73.8), and 2.6-fold cardiovascular mortality (2.63; 2.38–2.91; P<0.001; 43.9 vs. 8.3). These factors also had positive additive and multiplicative interactions in relation to all-cause mortality (their combined effect exceeded the sum or product of their separate effects; P<0.001), and were associated with higher mortality even among men with normal BMI. CONCLUSIONS: Low aerobic fitness, low muscular strength, and obesity at age 18 were associated with increased mortality in adulthood, with interactive effects between aerobic fitness and muscular strength. These findings suggest that preventive interventions should begin early in life and include both aerobic fitness and muscular strength, even among those with normal BMI.